206k views
1 vote
Solve the following system of equations using substitution.

4x + 2y = 12
x = y + 3

2 Answers

2 votes

Answer: look at the picture, sorry I can’t solve x = y + 3 for x.

Step-by-step explanation: Hope this help :D

Solve the following system of equations using substitution. 4x + 2y = 12 x = y + 3-example-1
Solve the following system of equations using substitution. 4x + 2y = 12 x = y + 3-example-2
Solve the following system of equations using substitution. 4x + 2y = 12 x = y + 3-example-3
User Kalai Selvan Ravi
by
6.6k points
7 votes

Answer:

x = 3

y = 0

Explanation:

The method of substitution is when one solves an equation for one of the variables, and then substitutes the expression into the other equation. After doing so, one will solve the other equation for the remaining variable and then backsolve for the first variable.

4x + 2y = 12

x = y + 3

The second equation is already sovled for parameter (x), subttiute this into the other equation,

4(y + 3) + 2y = 12

Distribute,

4y + 12 + 2y = 12

Simplify,

6y + 12 = 12

Inverse operations,

6y + 12 = 12

-12

6y = 0

/6

y = 0

Backsolve for (x), substitute the value of (y) into the equation for (x) and solve,

x = y + 3

x = 0 + 3

x = 3

User Rob Grzywinski
by
5.5k points